Fitting observed inflation expectations - Marco Del Negro; Stefano Eusepi (Federal Reserve Bank of New York, 2010)
This paper provides evidence on the extent to which inflation expectations generated by a standard Christiano et al. (2005)/Smets and Wouters (2003)-type DSGE model are in line with what is observed in the data. We consider three variants of this model that differ in terms of the behavior of, and the public's information on, the central banks' inflation target, allegedly a key determinant of inflation expectations. We find that: 1) timevariation in the inflation target is needed to capture the evolution of expectations during the post-Volcker period; 2) the variant where agents have imperfect information is strongly rejected by the data; 3) inflation expectations appear to contain information that is not present in the other series used in estimation; and 4) none of the models fully captures the dynamics of this variable.
Keywords: C32; E21; 330; Inflation expectations; imperfect information; Bayesian analysis; DSGE models